Enhancing the Legal Framework for Quality Assurance in Malaysian Online Sale of Goods Contracts - Abdullah Asuhaimi, Farhanin binti; Sari, Maulidina; Ghapa, Norhasliza binti; Makhtar, Maheran binti; Asari, Khairun Nisaa binti (Jambe Law Journal, 2026)
The rapid expansion of e-commerce in Malaysia has raised concerns about the quality of goods transacted through digital platforms. This paper critically examines the legal framework governing product quality in Malaysian online sale of goods contracts, focusing on the Sale and Goods Act 1957 and the Consumer Protection Act 1999. Unlike existing studies, this research provides a doctrinally integrated and comparative analysis that evaluates not only the substantive inadequacies of Malaysian law but also its structural limitations in addressing digital commerce, including the absence of regulatory recognition for digital goods and platform-based transactions. Using doctrinal legal analysis supplemented by comparative insights from the United Kingdom and the European Union, the paper identifies structural and doctrinal inadequacies in Malaysian statutory framework, particularly its failure to regulate digital goods and to provide enforceable remedies. The findings reveal significant enforcement gaps and practical difficulties experienced by consumers in online transactions. The study contributes novel insights by systematically linking doctrinal deficiencies with emerging digital market practices and proposing a reform framework that incorporates platform accountability, digital goods classification, and harmonised quality standards. Accordingly, the study proposes targeted statutory reforms, clearer definition standards for goods, and enhanced enforcement mechanisms, all of which are supported by lessons drawn from the UK Consumer Rights Act 2015 and the EU Consumer Rights Directive and Digital Content Directive. These recommendations aim to align Malaysian law with international best practices, reduce consumer vulnerability and enhance market transparency